PENGARUH JUMLAH PENGUSAHA KENA PAJAK, TINGKAT INFLASI DAN NILAI TUKAR RUPIAH ATAS DOLLAR AS TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI TAHUN 2015-2019 - Ana Arifatunnisa; Banu Witono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Value Added Tax (VAT) is a tax imposed for domestic consumption in the form of gods or services. Value added Tax is imposed on domestic consumption by individual, corporate and government tax payers. The purpose of this study was to examine the effect of the number of Taxable Entrepreneurs (PKP), the inflation rate and the exchange rate of the rupiah against the US dollar on Value Added Tax receipts at the Directorate General of Taxes, Central Java Regional Office II. The data used is secondary data from 2015-2019. This type of research uses causality research that explains the relationship between the amount of PKP, inflation rate and the exchange rate of the rupias against US dollar on the Value Added tax (VAT). The data analysis technique used is multiple linear regression analysis. Based on the result by data, the variable number of PKP has significant effect on VAT receipts, while the inflation rate and the rupiah exchange rate against the US dollar have no effect on VAT receipts.